Penerapan Rehabilitasi terhadap Korban Penyalahgunaan Narkotika Berdasarkan Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika dalam Perspektif Teori Rehabilitasi - Marsono; Iman Santoso; Kemala Atmojo (Syntax Literate, 2023)
In Law Number 35 of 2009 concerning Narcotics (Narcotics Law), drug users can be divided into Abusers, Addicts and Victims of Narcotics Abuse. Drug abusers are people who use drugs without rights or against the law. But if the person is a drug addict, he is a person who uses and abuses drugs dependently both physically and psychologically. Where drug abusers and addicts have an element of intentionality in their actions. This is of course different from the qualifications of people who are victims of drug abuse. The Supreme Court based on the provisions of Article 103 of the Narcotics Law took steps to build a paradigm to stop criminalization for drug addicts by issuing a Supreme Court Decree (SEMA) Number 4 of 2010 concerning the Determination of Abusers, and Drug Addicts into Medical Rehabilitation and Social Rehabilitation Institutions. The author provides an example of a case of a victim of drug abuse whose case has been decided by PN Klaten with its decision Number 8 / Pid.Sus / 2019 / PN.Kln. The research method used is the normative juridical method, which is research that prioritizes literature data, namely research on secondary data. The secondary data can be primary, secondary or tertiary legal material. This research includes research on positive legal provisions in force in Indonesia relating to the application of rehabilitation to victims of drug abuse. Based on the results of the study, the author concluded that the application of rehabilitation for victims of drug abuse was carried out by an integrated assessment team with the aim of saving victims of drug abuse, if someone is an addict. Or the victim caught can determine whether to be put in prison or rehabilitated. Addicts and victims of drug abuse are "sick people" who are obliged to undergo treatment by placing them in social rehabilitation institutions. This is based on the consideration that most drug offenders are victims of drug abuse. Understanding the reorientation of handling addicts and victims of drug abuse, which formulates that drug users who are in the legal process and proven to be pure users are no longer led to bars, but rehabilitated, so that both the Police and the Prosecutor's Office still apply legal processes and naan ids for every abuser caught consuming narcotics